Pengaruh Tanggung Jawab Sosial Perusahaan dan Profitabilitas Terhadap Penghindaran Pajak - Silvia Eka Putri Adi; Luayyi, Sri; Isnaniati, Siti (UMSurabaya Publishing, 2025)
This quantitative study investigates the relationship between corporate social responsibility (CSR), profitability, and tax avoidance practices among energy sector companies listed on the Indonesia Stock Exchange (IDX). The research focuses on the period from 2021 to 2023. Amidst heightened market competition, this study emphasizes the crucial need for companies to balance financial performance with social responsibilities. The analysis's conclusions indicate that CSR and profitability have a big impact on tax evasion. This report emphasizes how important CSR management and tax planning are to advancing company sustainability.